Níveis de fósforo em dietas para Kinguio (Carassius auratus) - Costa, Juliana Mara (2012)
Nutrition has a fundamental importance for the success of fish farming, considering that it represents the majority costs of production. Considering that the fish absorb various nutrients in the water, although the amount of phosphorus absorbed is not sufficient for its proper development, having the need to supply it in diet. Therefore, the present work aimed to evaluate the performance, chemical composition and plasmatic phosphorus response of the different levels of phosphorus inclusion on goldfish (Carassius auratus) diets. Were used 200 fry with weight, standard and total initial length of 3,11±0,50g; 3,68±0,23cm and 5,11±0,31cm, respectively. The fish were distributed in a completely randomized design with five treatments and four replicates in 20 cages of 0,15 m3 of useful volume, made of mesh shade and installed in a circular tank. The experimental lasted for 8 months, being divided into three phases. The diets were formulated with 30% of crude protein and 2900 kcal.kg-1 of digestible energy, isoproteic and isocaloric, with 0,65, 0,80, 0,95, 1,10 e 1,25% of phosphorus concentration. The fed was realized four times a day until the fish apparent satiation. The physical and chemical water variables such as pH, electrical conductivity and dissolved oxygen were measured weekly and the temperature was monitored four times a day. At the end of the experiment, the fish were fasted for 24 h, to empty the gastrointestinal tract. After this procedure, were collected and anesthetized with solution of benzocaine (75 mg.L-1) during 15 minutes, and after that the fish were weighed and measured. Was carried out the collection of 1,0 mL of fish blood via caudal vein using disposable syringes containing EDTA (10%). For determination of phosphorus in the blood, the phosphomolybdate colorimetric method was used. It is concluded that, for the first phase, on experimental conditions, the best results of weight gain were obtained for the phosphorus inclusion levels of 0,95 and 1,10%, (P<0,05) does not influence this parameter in the other phases. For feed conversion, the best index was obtained for the phosphorus inclusion levels of 1,25%, when evaluated the complete experimental period. There was no difference in phosphorus concentration in the fish plasm. The highest value of mineral matter in the chemical composition of the animals was observed for 1,25% of phosphorus supplement (P<0,05).